1993
DOI: 10.1227/00006123-199302000-00010
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Report on the Use of Laser-Doppler Flowmetry during Tethered Spinal Cord Release

Abstract: Neurological deterioration in the tethered cord syndrome has been postulated to result from a compromise of blood flow in the distal spinal cord. In order to evaluate vascular perfusion in human subjects, a new technique of laser-Doppler flowmetry was used to monitor continuously the microcirculation of the distal spinal cord during surgery for tethered cord release in 10 children. For further comparison, five children undergoing selective dorsal rhizotomy were also monitored. In the tethered cord syndrome gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 15 publications
2
15
0
Order By: Relevance
“…10, 22 The surgery itself is an effective procedure associated with low morbidity and prevents longterm morbidity resulting from the natural progression of the disease process. 7,8 In adult TCS, the late onset of symptoms is attributed to repeated microtrauma during flexion and extension of a mechanically tethered spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…10, 22 The surgery itself is an effective procedure associated with low morbidity and prevents longterm morbidity resulting from the natural progression of the disease process. 7,8 In adult TCS, the late onset of symptoms is attributed to repeated microtrauma during flexion and extension of a mechanically tethered spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Schneider et al 23 used laser Doppler flowmetry and identified a significant increase in the blood flow at the caudal spinal cord after untethering operations.…”
Section: 14mentioning
confidence: 99%
“…Acute tension on the spinal cord has been shown to produce spinal cord dysfunction and deranged metabolism in animal experiments, 15,23 but it is not known how these findings relate to the chronic situation typical of the patient with a tethered spinal cord. Superficial in vivo measurements of changes in cytochrome gradients 22 or laser Doppler blood flow 9 have been demonstrated in patients, but again the significance of these changes is not clear. Although increased tension on the conus from a thickened or fibrous filum 11 or asymmetric growth of the spine and spinal cord provides a plausible explanation for spinal cord dysfunction, plausibility does not equal causality.…”
Section: Tethered Spinal Cord Symptomatology Normal Imaging Findingsmentioning
confidence: 99%